Methylation of CLEC14A is associated with its expression and lung adenocarcinoma progression. Issue 3 (7th September 2018) - Su, Chongyu; Shi, Kang; Cheng, Xu; Han, Yi; Li, Yunsong; Yu, Daping; Liu, Zhidong
Abstract: Our main objective is probing the effect of methylation of CLEC14A on its expression and lung adenocarcinoma (LUAD) progression. Microarray analysis was utilized to screen out differentially downregulated genes with hypermethylation in LUAD tissues. The CLEC14A expression level was measured by western blot analysis and qRT‐PCR. Methylation‐specific‐PCR was performed to evaluate methylation status of CLEC14A . The 3‐(4, 5‐Dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromid (MTT) assay was used to check the relation between CLEC14A expression and cell proliferation. Cell cycle, cell apoptosis, migration, and invasion were respectively detected by the flow cytometry assay, wound healing assay, and transwell assay. Tumor xenograft models were established for investigating the effect of CLEC14A on tumor formation. CLEC14A expression in LUAD tissues was impaired compared with that in adjacent tissues, and CLEC14A promoter was highly methylated in LUAD. Overexpressing CLEC14A or inhibiting the methylation level of CLEC14A in A549 and LTEP‐a‐2 cells impeded the duplication of LUAD cells, promoted apoptosis, attenuated cell migration, and invasion ability, and arrested cell cycle at the G0/G1 phase. Overexpression of CLEC14A inhibited tumorigenesis of LUAD cells in nude mice. The promoter of CLEC14A is methylated in LUAD, leading to downregulation of CLEC14A in LUAD. CLEC14A acts as an antitumor role in LUAD by suppressing cell proliferation, migration, invasion, promoting cell apoptosis, and reducing tumorigenicity in nude mice. Thus, the inhibition of CLEC14A methylation is a novel strategy for the clinic treatment of LUAD. Abstract : 1. CLEC14A expression was reduced in LUAD. 2. CLEC14A methylation is responsible for the reduction. 3. Our findings suggested that CLEC14A might provide a potential diagnosis and treatment of LUAD.